3x + 4y - 23 = 0
3x + 4y +23 = 0
3x - 4y +23 = 0
3x - 4y - 23 = 0
Correct answer is D
34=y+5x−1
3(x - 1) = 4(y + 5)
3x - 3 = 4y + 20
3x - 4y - 23 = 0
Which of the following is not a sufficient condition for two triangles to be congruent? ...
If 2x + y = 10, and y ≠ 0, which of the following is not a possible value of x?...
A variable y is inversely proportional to x2, when y = 10, x = 2. What is y when x = 10?...
M varies directly as n and inversely as the square of p. If M = 3, when n = 2 and p =...
The straight line y = mx - 4 passes through the point(-4,16). Calculate the gradient of the line ...
The graph given is for the relation y = 2x2 + x - 1. Find the minimum value of y...